Management of Diseases through Non-chemical Means - Ram Chet Chaudhary (Research Aspects in Agriculture and Veterinary Science Vol. 6, 2022)
The chapter describes the concept of disease management through non-chemical means. Various methods, approaches and means are described in detail, which don’t use any synthetic chemicals to manage the diseases. Classification of host-parasite interactions are described to understands its mechanism. Methods to breed disease resistant varieties are described briefly and systems to deploy the resistant varieties to control diseases have been detailed. Advantages and limitations of disease control through resistant varieties are discussed. Control of diseases through cultural means and biological methods are enumerated. Described with suitable examples are the mechanisms of biological control through microbial suppression, induced host resistance, competition, hyper parasitism, antibiotic mediated suppression etc. Many of these methods can be used in organic production of crops that is the current trend in managing disease through organic means.